Development of Education and Health Sector for Socio-Economic Transformation in Nepal - Acharya, Bisna; Kharel, Khom Raj; Upadhyaya, Yadav Mani (Nepal Journal of Multidisciplinary Research, 2023)
The objective of this research is to examine the socioeconomic transformation of Nepal by analyzing the progress made in its education and health sectors. Education is the means to alter society, economic progress, and human wellbeing. The enhancement of a nation's socioeconomic position may be achieved through improving its education system and using technology. The experiences seen in both industrialized and developing countries provide evidence that educational development initiatives have a transformative impact on the socioeconomic position of these nations. The experiences of Nepal indicate that the development of education has played a crucial role in facilitating both social change and economic prosperity. This study employs a descriptive approach by using secondary data and adopting a secondary research strategy. The study's findings suggest that education development plays a crucial role in driving socioeconomic change within the specific context of Nepal. However, Nepal has not yet attained a desirable result in terms of education development and social change. In order to achieve significant socioeconomic progress, Nepal should prioritize the improvement of its education system.